2016
DOI: 10.1002/jsfa.7971
|View full text |Cite
|
Sign up to set email alerts
|

Assessing gelling properties of chia (Salvia hispanicaL.) flour through rheological characterization

Abstract: Based on texture and rheological properties, gels with 130 g kg of chia flour processed at 90 °C for 30 min showed the most suitable characteristics for use in the development of new food applications. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
(84 reference statements)
2
17
0
1
Order By: Relevance
“…This is the first comparative study to report lipid content in organically and conventionally-grown chia seeds. Organic and conventional growing systems produced chia seeds with a lipid content that ranged between 34.06 and 36.74 g/100g sample, which is comparable to that reported by Ramos et al, (2017), but relatively higher than that found in chia seeds from Australia (33.65%), Chile (30.22%) and Brazil (31.2%) (Coorey et al, 2014;da Silva et al, 2017;Marineli et al, 2014).…”
Section: Proximal Compositionsupporting
confidence: 57%
See 2 more Smart Citations
“…This is the first comparative study to report lipid content in organically and conventionally-grown chia seeds. Organic and conventional growing systems produced chia seeds with a lipid content that ranged between 34.06 and 36.74 g/100g sample, which is comparable to that reported by Ramos et al, (2017), but relatively higher than that found in chia seeds from Australia (33.65%), Chile (30.22%) and Brazil (31.2%) (Coorey et al, 2014;da Silva et al, 2017;Marineli et al, 2014).…”
Section: Proximal Compositionsupporting
confidence: 57%
“…In agreement with WHC values, the SWC in organic chia seeds was higher than that found in conventionally-grown crops (Table 4). In fact, the ability of chia seed to form gels is highly dependent on its swelling power and solubility (Ramos et al, 2017). Although the SWC in organic Peruvian chia seeds was lower than that found in processed chia flour (Ramos et al, 2017), organic chia products could be used as food ingredients for obesity prevention/weight control because they could modulate satiety and probably the microbiota composition and activity given their protein and antioxidant dietary fiber content (Acosta-Estrada et al, 2011).…”
Section: Functional Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on the full valorization of L. ochroleuca, the 2 mm fraction of the alga was subjected to autohydrolysis (AH) in a pressurized reactor (Parr Instruments series 4848, Moline, IL, USA) [14] and the liquid extract (liquor) obtained was stored at −18 • C until further use. When using the <0.25 mm alga fraction, purée-like mixtures were prepared following the procedure already described by the authors [17], with (LoUS) and without ultrasonic treatment (Lo).…”
Section: Laminaria Ochroleuca Sample Productionmentioning
confidence: 99%
“…Among the edible biopolymers, the use of plant seed mucilages namely chia and flax seed [14,15] are one of today's trends. Aside from the sustainability issue, these ingredients also have health benefits such as the regulation of colonic microbiota, reduction of hyperlipidemia, anti-inflammatory effect, control of glycemic response, and control of satiation [16].…”
Section: Introductionmentioning
confidence: 99%